Niemiecka wizja miejsca Rosji w multipolarnym świecie - Madajczyk, Piotr (Rocznik Polsko-Niemiecki, 2017)
The commonly held truth is that the attitude of German society and the German elite to Russia is different to the attitude of Poland. This is not entirely true because due to Russian policy, the Germans have become more critical of Russia in the twenty-first century than before. Germany, however, pursues a more global policy than Poland. As Russia and Germany are of great significance in Polish politics, it is important to question the German vision of Russia’s place in today’s multipolar world. This is all the more important given that Germany, as the strongest country in Europe and the one that stabilized the euro zone, has difficulty in defining its role in the international arena. It is only as a result of the recent debate about the hybrid war, that Germany has overcome its unilateral geo-economic perception of the world. It is clear that the Germans are facing a new challenge, which they have not been prepared for.